PERAN BALKON PADA RUMAH SUSUN DAN APARTEMEN (Role of Balcony of Flats and Apartments) - Lucky Septyadinda AD; Ilga Kumala Sari; Paulus Hariyono (Unika Soegijapranata Semarang, 2013)
ABSTRACT Green space management in flats and aparlments was a hard and complicated thing to implement. Therefore, there was hardly to find people utilizing the parls of flats and apartments as green spaces. Flats and aparlments are considered as verlical buildings having minimal land so that they often unconcern with the needs of green spaces although such spaces were ve/' necessa/'. This study was intended to learn the use of the balconies of the flats and aparlments to be alternative green open spaces. The problem arising was how a balcony was possibly to be used as a medium of open green space. The study applied three approaches. First was literatures study that was done to obtain seconda/' data. Second was comparative study by comparing several flats and apartments and the third was a case study by solving the cases of buildings' balconies that could be associated with the issues. An analysis was then conducted to find a solution of the existing problems. The findings of the study showed: firstly, greening could be done on the balcony to reduce excessive heat. Secondly, a balcony having greene/' would certainly add the aesthetic value. The balcony utilization for greening in flats and apartments could be a good alternative. Keywords: balcony, flats, aparlements ABSTRAK Pengelolaan ruang hijau pada rumah susun dan apartemen merupakan suatu hal yang rumit untuk diterapkan. Karena itu jarang sekali ada pengelola yang memanfaatkan bag ian-bag ian dari rumah susun dan apartemen sebagai ruang hijau. Rumah susun dan apartemen dianggap bangunan vertikal yang minim lahan sehingga sering terlupakan ruang hijau yang sangat penting. Penelitian ini ingin mempelajari pemanfaatan balkon rumah susun dan apartemen untuk digunakan sebagai altematif ruang terbuka hijau. Permasalahan yang muncul adalah seberapa jauh balkon dapat digunakan sebagai media ruang hijau terbuka. Penelitiaan menggunakan tiga pendekatan, yaitu pertama, studi literatur yang dilakukan untuk mendapatkan data-data sekunder. Kedua, studi banding dengan membandingkan beberapa rumah susun dan apartemen. Ketiga, studi kasus, dengan memecahkan kasuskasus balkon pada bangunan yang ada yang berhubungan dengan permasalahan terkait, kemudian mencari jalan keluar dengan analisis. Temuan penelitian menunjukkan, pertama, penghijauan dapat dilakukan di balkon untuk menanggulangi panas yang berlebihan. Kedua, balkon dengan penghijauan menambah nilai estetika. Pemanfaatan balkon untuk penghijauan pada rumah susun dan apartemen merupakan alternatif yang baik. Kata Kunci : balkon, rumah susun, apartemen.